Validation of the schema coping inventory for dysfunctional coping strategies - Simone Gazzellini; Valerio Pellegrini; Eleonora Napoli; Vanessa Ventre; Donatella Lettori; Enrico Castelli; Barbara Basile; Mauro Giacomantonio (Frontiers in Psychology)
IntroductionAccording to the theoretical model of Schema Therapy, each human being has basic needs that require natural satisfaction from childhood. When these emotional needs are frustrated, early maladaptive schemas (EMS) develop, leading to coping styles that are strategies to manage the pain caused by activated EMS. The study validates and standardizes the Schema Coping Inventory in the Italian population and evaluates correlations between psychological variables and the SCI.MethodsWe analysed data from a community sample of 602 Italian adults, aged between 18 and 69 years, who endorsed a structured questionnaire, involving demographic information, the Italian version of the SCI, and an array of theoretically related psychological constructs.Results and discussionConfirmative factor analysis corroborated the tridimensional structure of the SCI (Surrender, Avoidance, Overcompensation), both in terms of the overall goodness-of-fit of the model and the single items’ factor loading in the corresponding factors. The internal consistency turned out to be satisfactory. Construct validity was assessed through convergent and divergent (positive and negative) correlations with other coping style measures and psychopathological scales. Mean values and mean standard deviations are reported for the general population, for psychopathological clinical and non-pathological samples.